Impact of cirrhosis in patients undergoing laparoscopic liver resection in a nationwide multicentre survey. Issue 3 (9th January 2020) - Hobeika, C; Fuks, D; Cauchy, F; Goumard, C; Soubrane, O; Gayet, B; Salamé, E; Cherqui, D; Vibert, E; Scatton, O
Abstract: Background: The aim was to analyse the impact of cirrhosis on short-term outcomes after laparoscopic liver resection (LLR) in a multicentre national cohort study. Methods: This retrospective study included all patients undergoing LLR in 27 centres between 2000 and 2017. Cirrhosis was defined as F4 fibrosis on pathological examination. Short-term outcomes of patients with and without liver cirrhosis were compared after propensity score matching by centre volume, demographic and tumour characteristics, and extent of resection. Results: Among 3150 patients included, LLR was performed in 774 patients with (24·6 per cent) and 2376 (75·4 per cent) without cirrhosis. Severe complication and mortality rates in patients with cirrhosis were 10·6 and 2·6 per cent respectively. Posthepatectomy liver failure (PHLF) developed in 3·6 per cent of patients with cirrhosis and was the major cause of death (11 of 20 patients). After matching, patients with cirrhosis tended to have higher rates of severe complications (odds ratio (OR) 1·74, 95 per cent c.i. 0·92 to 3·41; P = 0·096) and PHLF (OR 7·13, 0·91 to 323·10; P = 0·068) than those without cirrhosis. They also had a higher risk of death (OR 5·13, 1·08 to 48·61; P = 0·039). Rates of cardiorespiratory complications ( P = 0·338), bile leakage ( P = 0·286) and reoperation ( P = 0·352) were similar in the two groups. Patients with cirrhosis had a longer hospital stay than those without (11 versus 8 days; P = 0·018). Centre expertise was an independent protective factor against PHLF in patients with cirrhosis (OR 0·33, 0·14 to 0·76; P = 0·010). Conclusion: Underlying cirrhosis remains an independent risk factor for impaired outcomes in patients undergoing LLR, even in expert centres. Graphical Abstract: The aim was to analyse the impact of cirrhosis on short-term outcomes after laparoscopic liver resection in a multicentre national cohort study. Short-term outcomes of patients with and without cirrhotic liver were compared after propensity score matching by centre volume, demographic and tumour characteristics, and extent of resection. Underlying cirrhosis remains an independent risk factor for impaired outcomes in patients undergoing laparoscopic liver resection, even in expert centres. Cirrhosis leads to impaired outcomes even in expert centers